6. Factorise Expressions Begin to factorise an expression by taking out the common number factors 6b Factorise an expression by taking out the common number factors 6a Factorise an expression by taking out the common algebraic factors 7c Find the values of constants in an identity by factorising 7c Substitute positive and negative numbers into expressions involving small powers and brackets 7c Reference Material Text book: section 7.5 page 118 MEP: 8.8 section 3
Factorise an expression by taking out the common number factors 6a 6a + 12 = 6(a + 2) 5b – 15 = 5(b – 3) 4a + 2b = 2(2a + b) 3x – 2y = 3x – 2y no common factors here 4c – 10t = 2(2c – 5t) 12f + 15 = 3(4f + 5) 9y – 21n = 3(3y – 7n) 5y – 5 = 5(y – 1) 15 – 5p = 5(3 – p)
3x + x² = x(3 + x) 4y² - 2y = 2y(2y – 1) 6f² - 3f = 3f(2f – 1) Factorise an expression by taking out the common algebraic factors 7c 3x + x² = x(3 + x) 4y² - 2y = 2y(2y – 1) 6f² - 3f = 3f(2f – 1) 2f²g + 4fg² = 2fg(f + 2g) 22 May 2019